2019
DOI: 10.3390/app9071308
|View full text |Cite
|
Sign up to set email alerts
|

Production and Processing of a Spherical Polybutylene Terephthalate Powder for Laser Sintering

Abstract: This work describes the production of a spherical polybutylene terephthalate (PBT) powder and its processing with selective laser sintering (SLS). The powder was produced via melt emulsification, a continuous extrusion-based process. PBT was melt blended with polyethylene glycol (PEG), creating an emulsion of spherical PBT droplets in a PEG matrix. Powder could be extracted after dissolving the PEG matrix phase in water. The extrusion settings were adjusted to optimize the size and yield of PBT particles. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…[154c] Polyolefin powders can alternatively be produced by melt emulsification. [156] Melt emulsification is currently being used by ASPECT, an SLS material supplier, to produce spherical PP powders which are commercialized as Asphia PP. [133] PE is a commodity polymer that has lower melting temperatures than PP, and is typically classified by its density and chain branching.…”
Section: (29 Of 54)mentioning
confidence: 99%
“…[154c] Polyolefin powders can alternatively be produced by melt emulsification. [156] Melt emulsification is currently being used by ASPECT, an SLS material supplier, to produce spherical PP powders which are commercialized as Asphia PP. [133] PE is a commodity polymer that has lower melting temperatures than PP, and is typically classified by its density and chain branching.…”
Section: (29 Of 54)mentioning
confidence: 99%
“…Metals and metal-alloys are processed using direct metal laser sintering (DMLS) since most of them, such as titanium and its alloys, have high melting points. When the technology is applied solely to polymers, then it is referred to as PLS [9]. In PLS, complex 3D components are manufactured through the coalescence of layers of the materials using a high-energy laser beam.…”
Section: Polymer Laser Sinteringmentioning
confidence: 99%
“…However, the material range remains limited due to the stringent processing requirements, as well as the challenge of powder degradation due to high processing temperatures. Besides, in PLS, about 80-90 percent of the powder charge is not used in printing of components [9]. Therefore, there is a need to reuse this high percentage of unused powder in order to avoid wastes and due to its high cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wegner et al [25] reported powder bed fusion of PBT powders led to high modulus of up to 3000 MPa, but the strength values were below 40-45 MPa and the elongation-to-break was 1%-2%. Kleijnen et al [26] made a PBT powder for powder bed fusion that had a processing window of only 7.6 • C, and printing simple bars was difficult enough, due to curl. The bars that could be printed showed a modulus of 2211 MPa, a strength of 20.3 MPa, and an elongation-to-break of 1%.…”
Section: Pet Versus Other Thermoplastics For Powder Bed Fusionmentioning
confidence: 99%